The Last Sister : A Novel - McKinney-Whitaker, Courtney (Book collections on Project MUSE., 2014)
In 1759, after a band of fellow settlers fakes a Cherokee raid to conceal the murder of her family, seventeen-year-old Catriona "Catie" Blair embarks on a journey across rural South Carolina and through Cherokee territory to report the crime and bring the murderers to justice, while desperately seeking to regain her own sense of safety.